2020
DOI: 10.1177/1470412920941901
|View full text |Cite
|
Sign up to set email alerts
|

Pretty in pink: David Antonio Cruz’s portrait of the florida girls

Abstract: Roused by the deaths of five African American transgender women in Florida in 2018, artist David Antonio Cruz intervenes in inaccurate media reports about these murders. Painting portrait of the florida girls in 2019, his diptych of significant scale and palette, confronts this senseless violence and challenges sensationalized coverage. This article centralizes his work arguing for the ways in which Cruz innovates transgender of color visibility through a queer of color critiquing of the portrait form and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this data set, being an ethnic minority, low on socioeconomic status, overweight or older in age may pose additional challenges to the gender affirmation journey. Research has shown that these identifiers often carry with them their own stigma and otherness and, therefore, can cause additional negative stress for the TGD individual (Garthe et al , 2020; Hernandez, 2020; Lazaro and Bacio, 2021; Lee et al , 2021; Cusack et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this data set, being an ethnic minority, low on socioeconomic status, overweight or older in age may pose additional challenges to the gender affirmation journey. Research has shown that these identifiers often carry with them their own stigma and otherness and, therefore, can cause additional negative stress for the TGD individual (Garthe et al , 2020; Hernandez, 2020; Lazaro and Bacio, 2021; Lee et al , 2021; Cusack et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…and gender diverse consumers their own stigma and otherness and, therefore, can cause additional negative stress for the TGD individual (Garthe et al, 2020;Hernandez, 2020;Lazaro and Bacio, 2021;Lee et al, 2021;Cusack et al, 2022).…”
Section: Transgendermentioning
confidence: 99%